P-61 System leadership the opportunity for hospices and hospice leaders. Issue Volume 5: Issue (2015)Supplement 3 (1st November 2015) - Dewar, Steve; Taylor, Judy; Harries, John; Wilson, Janet; Wisher, Amanda
Abstract : Introduction: Integrated health and social care systems are central to enabling person-centred care for people with complex needs. This paper reviews the evidence for systems leadership as a vital component in the delivery of these integrated systems. Delivering integrated health and social care for end of life care is seen as a remedy for the failings demonstrated in the Health Service Ombudsman's report. Putting the development of integrated systems for end of life at the heart of the NHS agenda is recommended in both the 2015 Health Select Committee report on Palliative Care and the 2015 Choice Review. Hospices bring unique strengths to system leadership, not least their ability to use independence, resources, and expertise to bring the system together in the pursuit of improvement. Hospice leaders can offer system leadership and are well placed to work across organisational boundaries and contribute to the development of integrated care. Aims: This paper will showhow the hospice sector can use system leadership to create the necessary conditions for change and how hospice leaders can use their connexions and skills to deliver it. Methods: The literature review identifies themes in the discussion of systems leadership in relation to end of life care and the role of the hospice and of hospice leaders. These themes include the legitimacy of the hospice as a system leader and the potential role of hospice leaders in shaping new integrated systems of care. The paper will present a discussion of the way in which hospices and individuals might grasp this opportunity. The discussion will be based on deliberative focus groups with a purposive sample of hospice leaders. Conclusion: This paper highlights the opportunity that system leadership creates for both hospices and their leaders to shape the development of integrated health and social care at the end of life.